Efeito do ultrassom pulsado de baixa intensidade sobre o infiltrado inflamat??rio presente no m??sculo esquel??tico ap??s les??o aguda - Silva Junior, Evaldo Moreira da (2015)
Muscle lesions although more common in athletes also affects sedentary people, leading to partial or total removal of the individual from their daily activities. The muscle repair process comprises interdependent phases orchestrated by immune cells that invade the tissue behind the injury occurrence. Delays or enhancements at different stages can lead to chronic inflammation cases or fibrosis, reinforcing the search for an alternative treatment. The therapeutic ultrasound (US) is widely used to treat muscle injuries, but lack scientific evidence to explain its mechanism of action. This study aimed aims to elucidate the role of US in the inflammatory infiltrate cells presentes on the muscle tissue behind acute injury. For this purpose, 45 Wistar rats will were used, separated into 3 groups (5 animals in the control group, 20 animals suffer injury and will not receive treatment and 20 animals suffer injury and will be treat with US). The adopted procedure is the cryoinjury lesion consisting of two bat applications of cooled in liquid nitrogen directly into the in tibialis anterior (TA) muscle. The US treatment and these groups will be evaluate after 1, 2, 3 and 7 days. The US treatment (stationary mode, pulse 1: 4, with a frequency of 1 MHz and intensity of 0.4 W / cm2) was performed daily for 3 minutes. At the end of the study, the animals were euthanized with an anesthetic overdosis and the TA muscles were removed for neutrophil infiltration analysis and the different phenotypes of macrophages during muscle remodeling by immunostaining (positive for CD68, CD80, CD163, CD206 and elastase). The images were analyzed and quantified using the Image J software (National Institute of Health - NIH, USA). Statistical analysis of data was performed according to evaluating the distribution of the same by & Kolmogorov Smirnov test. Treatment with US generated in the damaged areas of the treated muscles, reduction in the number of neutrophils (elastase +) during the periods 1 and 2 days, an increase of M1 macrophages (CD80 +) in one day period and reducing them in periods of 2, 3 and 7 days. It was also noted when comparing the injured muscles untreated, the US generated reduced profile macrophages M2a (CD206 +) on day 2 and increased this phenotype cells present on day 3. The labeling of total macrophages (CD68 +) uS-treated animals was lower than that present in untreated animals on days 2, 3 and 7. There was no difference in other temporal comparisons. As continuity and the intensity of cells presence with pro or anti inflammatory action can leading to chronic inflammation or fibrosis cases, attesting the US's ability can modulate the occurrence of these cells is an important step in understanding the therapeutic potential of this resource in the treatment of muscle injuries.